Phytopharmacological Review of a Food Supplement Zingiber officinale Roscoe (Zingiberaceae) - Pai, Vasudev; Subraya, Chandrashekar K.; Sri, Baby Sai; Nanjundaiah, Aswatha Ram H. H. (Current Nutrition & Food Science, 2022)
Zingiber officinale, a medicinal herb commonly used in Ayurveda belongs to family Zingiberaceae and is reported to have various therapeutic properties. Roots as well as rhizomes of this plant are commonly used in the treatment of digestive disorder. It has also been used as expectorant, spasmolytic, anti-tussive, anti-allergic, antihistaminic activity and inhibits coughing. The roots and rhizomes are rich sources of essential oil, which may be one of the reasons for medicinal properties. Required data on this plant were obtained from electronic sources (google scholar, PubMed, Scopus, Web of Science), several classical textbooks on Ayurveda, and ethnopharmacology. This review article covers all the relevant information on its pharmacological and phytochemical aspects. In this study, we have critically reviewed recent advancements of Zingiber officinale in an attempt to authenticate its use as a multipurpose therapeutic ingredient.
Keywords: phytochemistry